The Investigation of Politeness Principles and Strategies Used in Akeelah and the Bee Movie - Esa Nur Hikmahwati; Dhafid Wahyu Utomo; Sutrisno Sadji Evenddy (LPPM Universitas Bina Sarana Informatika, 2021)
This research was aimed to investigate what kind of politeness principle and most dominant type applied in the utterances of the main characters’ Akeelah and the Bee movie and strategies applied in their utterances of the main characters’ Akeelah and the Bee movie. A descriptive qualitative was employed in this research. It concerned with the description of the data in the form of utterances produced by the characters in which politeness principles and strategies exist. There were two sources in this research. The primary source was the script of the movie. The secondary sources were books. The results of this research were: first, the main characters applied agreement maxim, approbation maxim, tact maxim, modesty maxim, and sympathy maxim in their utterances and the most dominant type used is agreement maxim. Second, in the application of politeness strategies, the main characters applied Bald-on-record, positive politeness, negative politeness, and off-record in their utterances. Keywords: Akeelah and the Bee, politeness principles, politeness strategies.